1965
DOI: 10.1103/physrev.138.a1170
|View full text |Cite
|
Sign up to set email alerts
|

High-Field Superconductivity of Carbides

Abstract: The high-magnetic-field properties of some refractory carbides were investigated at low temperatures. The upper critical fields for NbC, a solid solution of 40% NbC-60% TaC, and TaC are between 4.2 and 21.3 kG; MoC, M056C44, and Mo 6 oC4o+2% VC have upper critical fields between 80 and 120 kG; and Mo 3 Al 2 C has an upper critical field of 156 kG at 1.2°K. Mo 3 Al 2 C is the only known superconductor with the 0-Mn crystal structure. From the available data the electronic specific-heat coefficient 7, the thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
17
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 12 publications
4
17
0
Order By: Relevance
“…[2][3][4][5] Recently it has attracted renewed attention, 6-10 because its cubic β-Mn-type crystal structure does not contain a center of inversion. In such noncentrosymmetric superconductors, as first discussed for CePt 3 Si, 11 the electron pairing process is described to be a mixture of spin-singlet and spin-triplet states. 12,13 The question whether Mo 3 Al 2 C can be classified as a conventional or unconventional superconductor remains unresolved according to very recent investigations.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Recently it has attracted renewed attention, 6-10 because its cubic β-Mn-type crystal structure does not contain a center of inversion. In such noncentrosymmetric superconductors, as first discussed for CePt 3 Si, 11 the electron pairing process is described to be a mixture of spin-singlet and spin-triplet states. 12,13 The question whether Mo 3 Al 2 C can be classified as a conventional or unconventional superconductor remains unresolved according to very recent investigations.…”
Section: Introductionmentioning
confidence: 99%
“…The origin of the superconductivity at T cu (H) may be due to Ta-C layers in Ta 2 S 2 C. According to Giorgi et al,12 the critical temperature T c of the pristine TaC 1−x increases with decreasing x and is equal to 9.0 K at x = 0.019. Fink et al13 have reported that the values of H c1 and H c2 at T = 1.2 K for TaC are 220 Oe and 4.6 kOe. These values are in good agreement with the values of T cu and H(u)…”
mentioning
confidence: 99%
“…Later, Fink et al reported the upper critical field (H c2 ) = 15.6 T at 1.2 K, which was determined from critical current density measurements 27 . From the experimentally determined values of the upper critical field (H c2 ), the normal-state resistivity (ρ n ), the critical current density (J c ), and the transition temperature (T c ), they estimated the electronic specific heat coefficient (γ), lower critical field (H c1 ), and Ginzburg-Landau parameter (κ) at 1.2 K 27 . Several carbides and nitrides with isotypic H-phases and phases with the filled and ordered -Mn structure were tested for superconductivity by L.E.…”
Section: Introductionmentioning
confidence: 99%